Phytochemical, GC-MS analysis and antioxidant activities of leaf methanolic extract of Lai (Durio kutejensis), the endemic plant of Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Manurung H, Susanto D, Kusumawati E, Aryani R, Nugroho RA, Kusuma R, Rahmawati Z, Sari RD. 2022. Phytochemical, GC-MS analysis and antioxidant activities of leaf methanolic extract of Lai (Durio kutejensis), the endemic plant of Kalimantan, Indonesia. Biodiversitas 23: 5587-5594. Lai (Durio kutejensis Hassk. Beck) is a fruit plant species endemic to Kalimantan, Indonesia. The leaves are traditionally used to treat several diseases. Currently, there is no scientific validation of the phytochemical content, bioactive compounds, and biological activities of leaf extracts of this plant from the East Kalimantan Province of Indonesia. So, this study aimed to determine the phytochemical compounds, bioactive compounds, and antioxidant activity of crude leaf methanol extract of D. kutejensis. Gas chromatography-mass spectrometry (GC-MS) analysis was performed to determine the bioactive compounds of lai leaf methanol extract. DPPH (2,2-diphenyl-1-picrylhydrazyl) was used to evaluate antioxidant activity. Screening of phytochemical compounds of the leaf methanol extract showed the presence of alkaloids, flavonoids, phenolics, saponins, and steroids. The leaf extract of lai contains total phenolic (104,55 µg GAE g-1 extract) and total flavonoid (281,41 µg QE g-1extract). The extract has weak antioxidant activity with an IC50 of 163,849 ppm. GC-MS analysis confirmed the presence of 43 identified compounds in the crude leaf methanolic extract of D. kutenjesis such as; 2-(1,1-dimethyl ethyl)-Phenol; 4-(3-hydroxy-1-propenyl)-2-methoxy-Phenol (Coniferyl alcohol); E7-Decenylacetate; Octadecanoic acid (Stearic acid); 1,3,6-Octatriene, 3,7-dimethyl-, (Z)-; Palmitaldehyde, diisopentyl acetal; Ledol; Estran-3-one, 17-(acetyloxy)-2-methyl-, (2.alpha.,5.alpha.,17.beta.)-. This study revealed that the leaf methanol extract of D. kutejensis is a good resource of many bioactive compounds that justifies the traditional usage of this species.
Keywords: Bioactive compounds, Durio kutejensis, endemic plant, GC-MS, Lai